Primary oral mucosa-associated lymphoid tissue (MALT) lymphoma in patient with monoclonale gammopathy: a rare case report - Hilal Hafian; Hubert Schvartz; Martine Patey; Anne Quinquenel (BMC, 2021)
Abstract Background Monoclonal gammopathy is a biological reality encountered in approximately 1% of the general population. In the absence of clinical and biological signs, it is considered of undetermined significance; however, it can be a biological signature of a monoclonal lymphocytic or plasma-cell proliferation. Their localisation to the oral mucosa remains rare and difficult to diagnose, particularly in indolent forms that escape imaging techniques. Case presentation Here, we report the case of a 73-year-old woman with a history of IgM kappa gammopathy followed for 13 years. The patient did not have a chronic infection or an autoimmune disease, and all the biological investigations and radiological explorations were unremarkable during this period. The discovery of a submucosal nodule in the cheek led to the diagnosis of MALT lymphoma and regression of half of the IgM kappa level after resection. The review of the literature shows the dominance of clinical signs (i.e., a mass or swelling) in the diagnosis of primary MALT lymphomas of the oral cavity after surgical resection. Conclusions Our case illustrates the role of examination of the oral cavity in the context of a monoclonal gammopathy. The absence of clinical and radiological evidence in favor of lymphoplasmacytic proliferation, does not exclude a primary indolent MALT lymphoma of the oral mucosa.